2013
DOI: 10.1073/pnas.1302337110
|View full text |Cite
|
Sign up to set email alerts
|

Ypt1 recruits the Atg1 kinase to the preautophagosomal structure

Abstract: When macroautophagy, a catabolic process that rids the cells of unwanted proteins, is initiated, 30-60 nm Atg9 vesicles move from the Golgi to the preautophagosomal structure (PAS) to initiate autophagosome formation. The Rab GTPase Ypt1 and its mammalian homolog Rab1 regulate macroautophagy and two other trafficking events: endoplasmic reticulum-Golgi and intra-Golgi traffic. How a Rab, which localizes to three distinct cellular locations, achieves specificity is unknown. Here we show that transport protein p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
141
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(150 citation statements)
references
References 31 publications
7
141
1
1
Order By: Relevance
“…Our model might appear to conflict with previous reports that TRAPPIII functions at the PAS in yeast and in forming autophagosome in mammalian cells (Lynch-Day et al, 2010;Kakuta et al, 2012;Lipatova et al, 2012;Huang et al, 2011;Wang et al, 2013). Our model does not necessarily exclude these possibilities, but our results suggest that the direct contribution of TRAPPIII to autophagosome formation is not as large as proposed in those studies.…”
Section: Discussioncontrasting
confidence: 56%
“…Our model might appear to conflict with previous reports that TRAPPIII functions at the PAS in yeast and in forming autophagosome in mammalian cells (Lynch-Day et al, 2010;Kakuta et al, 2012;Lipatova et al, 2012;Huang et al, 2011;Wang et al, 2013). Our model does not necessarily exclude these possibilities, but our results suggest that the direct contribution of TRAPPIII to autophagosome formation is not as large as proposed in those studies.…”
Section: Discussioncontrasting
confidence: 56%
“…TRAPPI and TRAPPII participate in ER-to-Golgi and intra-Golgi trafficking, respectively (Cai et al, 2007;Cai et al, 2005;Yamasaki et al, 2009), whereas TRAPPIII is the autophagyspecific GEF for Ypt1. During autophagy, TRAPPIII localizes to the PAS in yeast, to which it appears to be recruited by Atg17 (Lynch-Day et al, 2010;Tan et al, 2013;Wang et al, 2013). Once at this site, TRAPPIII mediates the recruitment of YPT1 Lynch-Day et al, 2010;Wang et al, 2013), which, in its activated GTP-bound form, is thought to recruit Atg1 .…”
Section: How Could Eres Contribute To Autophagosome Formation? Model mentioning
confidence: 99%
“…During autophagy, TRAPPIII localizes to the PAS in yeast, to which it appears to be recruited by Atg17 (Lynch-Day et al, 2010;Tan et al, 2013;Wang et al, 2013). Once at this site, TRAPPIII mediates the recruitment of YPT1 Lynch-Day et al, 2010;Wang et al, 2013), which, in its activated GTP-bound form, is thought to recruit Atg1 . Of further significance, the TRAPPIIIYpt1 module has also been detected in immunopurified Atg9-containing vesicles in yeast , which have been shown to contribute to the generation of the PAS in this organism (Mari et al, 2010;Yamamoto et al, 2012) and could be part of the early PAS or phagophore intermediate observed at the recycling endosomes in mammalian cells (Nair et al, 2011).…”
Section: How Could Eres Contribute To Autophagosome Formation? Model mentioning
confidence: 99%
See 1 more Smart Citation
“…The TRAPPIII complex associates withSec23, an integral component of COPII, and is a GTP Exchange Factor (GEF) of a small GTPase Ypt1 in yeast. Therefore COPII vesicles and Ypt1 are recruited to the PAS, where COPII vesicles supply membrane and Ypt1 regulates vesicular events [50,[74][75][76]. Furthermore, it is proposed that the TRAPPIII complex may also be a tether to facilitate heterotypic fusion between an Atg9 vesicle and a COPII vesicle in the PAS [50,77].…”
Section: Converging On the Pasmentioning
confidence: 99%